Predictors of low birth weight babies born in tribal tertiary health care setting: a cross sectional study - S. B., Thakre; S. S., Thakre; A. C., Kaware; H., Adikane (International Journal Of Community Medicine And Public Health, 2018)
Background: A baby’s weight at birth is a strong indicator of maternal and newborn health and nutrition. Strategies to reduce prevalence of LBW are important in order to achieve the third Sustainable Development Goals (SDG 3)-reduce child mortality. With this background the present study was undertaken to estimate proportion of LBW babies born at tribal tertiary health care institution and to find out predictors of the LBW among babies. Methods: The present cross sectional study was undertaken at tertiary health care setting. We restricted analyses to singleton live births, and following an initial descriptive summary of the deliveries, logistic regression analysis was conducted to investigate the association of various factors. Results: Our results show proportion of LBW was 17.84% in babies born at tribal tertiary health care setting. There is no significant difference of LBW in different socio-demographics of the mother. However; significant difference was observed in tribal and non-tribal women and women with low literacy lever; wherein significant predictors were related to utilization of antenatal care (ANC), ICDS services, etc. Statistical significance was ascertained based on a p<0.05. Conclusions: In this study; significant predictors were low maternal education, <4 ANC visits, inadequate consumption iron and folic acid, low hemoglobin percent level, and no additional diet at ICDS during current pregnancy. It has also provided basic information pertinent to quality of ANC care and it influence on LBW. Findings of this study are useful for maternal and child health policy makers, practitioners and those who provide health care during pregnancy